Less radical surgery for women with early stage cervical cancer: Our experience on radical vaginal trachelectomy and laparoscopic pelvic lymphadenectomy - I. Rizzuto; W. MacNab; R. Nicholson; M. Nalam; B. Rufford (Elsevier, 2019)
We report the use of radical vaginal trachelectomy (RVT) with pelvic laparoscopic lymphadenectomy (LPL) in patients with early stages cervical cancer (FIGO stage IA2-IB1). This is a case series prospectively collected over a 6-year period (2011-2017) at the Ipswich hospital, UK. Cases were compared to a group of women with a similar stage of cervical cancer, but treated with radical hysterectomy (RH) and pelvic lymphadenectomy (PL). A total of 19 patients (group 1) underwent RVT and LPL, and 51 (group 2) had RH and PL. We included: 5/19 (26%) stage IA2 and 14/19 (74%) stage IB1. Among those, we had: 12/19 (63%) cases of squamous cell carcinoma (SCC), 7/19(37%) of adenocarcinoma. Mean hospital stay was 2.7 days (range 2-4) in group 1 versus 4.8 days (range 3-8) group 2 (p-value = 0.173). The complication rate was not statistically different between the two groups 4/19(21%) and 7/51(14%) (p-value 0.169). The mean follow-up period was 47.3 months (range 7-78) in both groups. There were no cases of recurrence in group 1 and 2/51(4%) cases in group 2, but the difference was not significant (p-value = 0.497). In our experience RVT in well-selected patients is a safe treatment option with similar oncological outcomes when compared to patients undergoing more extensive surgery for the same early stage cervical cancer. Keywords: Early stage cervical cancer, Trachelectomy, Fertility sparing surgery